2012
DOI: 10.1212/wnl.0b013e318260cbe6
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported impact of symptoms in myotonic dystrophy type 1 (PRISM-1)

Abstract: Objective: To determine the most critical symptoms in a national myotonic dystrophy type 1 (DM1) population and to identify the modifying factors that have the greatest effect on the severity of these symptoms. Methods:We performed a cross-sectional study of 278 adult patients with DM1 from the national registry of patients with DM1 between April and August 2010. We assessed the prevalence and relative significance of 221 critical DM1 symptoms and 14 disease themes. These symptoms and themes were chosen for ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
205
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(216 citation statements)
references
References 27 publications
9
205
1
Order By: Relevance
“…In a recent study, Heatwole et al [40] demonstrated that fatigue was reported by DM1 patients as the primary symptom of their condition and the one having the greatest overall effect on their lives. It is thus unsurprising that fatigue was identified as the factor explaining the most variance (about 25%) with regard to the physical health domains (PCS model) of DM1 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Heatwole et al [40] demonstrated that fatigue was reported by DM1 patients as the primary symptom of their condition and the one having the greatest overall effect on their lives. It is thus unsurprising that fatigue was identified as the factor explaining the most variance (about 25%) with regard to the physical health domains (PCS model) of DM1 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The age at onset was determined by questioning the patients about their age at onset. Age at onset was defined when the patient complained of at least one of the following symptoms or signs: difficulty in walking or running, fine motor problems, difficulties loosing grip, swallowing difficulties, decreased strength, stiffness, cataract, arrhythmia, or episodes of apnea [7]. In addition, the disease duration was defined by the difference between age at onset and age at the time of MRI acquisition.…”
Section: Methodsmentioning
confidence: 99%
“…Daytime sleepiness and impaired sleep are common in patients with adult DM1 [9,12,[14][15][16] representing the 4th most prevalent symptomatic theme among patients with DM1 [17]. Impaired sleep disorders are clearly present in both adults and children and can be present as sleep-related breathing events, periodic limb movements or REM-sleep disturbances [9][10][11].…”
Section: (Mt Rogers B Gallais B Schoser P Wijkstra D Duboc)mentioning
confidence: 99%